Siblings of Children With a Complex Chronic Health Condition: Maternal Posttraumatic Growth as a Predictor of Changes in Child Behavior Problems. (22nd June 2016) - Stephenson, Ellen; DeLongis, Anita; Steele, Rose; Cadell, Susan; Andrews, Gail S.; Siden, Harold
Abstract : Objective The present study examined the role of maternal posttraumatic growth in changes in behavioral problems among the siblings of children with complex chronic health conditions. Methods Data were collected from a sample of 70 siblings from 58 families with at least one child diagnosed with a life-threatening genetic, metabolic, or neurological condition. Every 6 months for up to 4 years, sibling behavior problems were assessed through both parent-reports and youth self-reports. At each visit, mothers also completed self-reports of posttraumatic growth. Results Time-lagged multilevel regression analyses revealed that higher levels of maternal posttraumatic growth predicted subsequent declines in parent-reported internalizing, externalizing, and total behavior problems among healthy siblings. These findings were partially replicated using youth self-reports of their own behavior problems. Conclusion The findings suggest that the benefits of posttraumatic growth may extend beyond the self to other family members, particularly to children in the family.